MENINGKATKAN KEMAMPUAN BERPIKIR POSITIF PADA REMAJA KORBAN ERUPSI GUNUNG SINABUNG MELALUI PEMBERIAN LAYANAN KONSELING KELOMPOK DI POSKO PENGUNGSIAN KURUSUS WANITA KRISTEN (KWK) BERASTAGI KAB, KARO - Sari Bernadetta Lumban Gaol; Pasteria Sembiring (Jurnal Diversita, 2015)
The purpose of this study was to enhance positive thinking skills in adolescentsrefugees of Mount Sinabung through counselling service delivery in the KWK Berastagi Kab. Karo ". The number of research subjects were 10 people. Data collection tool used observation and questionnaires. The results obtained in the first observation is 51.67%, and after being given the service, the first cycle increased to 74.58%, but has not reached the "good" then made back in the second cycle, and achieved good category as 85.41%. Then the hypothesis that through the provision of counseling services can improve the group's ability to think positively on young refugees of Mount Sinabung Berastagi KWK, Kab.Karo otherwise acceptedKeyword: Group counseling service, Positive thinking skill, Refugee